Children's School Readiness: Implications for Eliminating Future Disparities in Health and Education. (February 2014) - Pagani, Linda S.; Fitzpatrick, Caroline
Background . School-entry characteristics predict adult educational attainment, which forecasts dispositions toward disease prevention. Health and education risks can also be transmitted from one generation to the next. As such, school readiness forecasts a set of intertwined biopsychosocial trajectories that can influence the developmental antecedents to health and disease prevalence in society. Purpose . To predict children's health behaviors and academic adjustment at the end of fourth grade from their kindergarten entry math, vocabulary, and attention skills. Method . We use a subsample of 614 girls and 541 boys from the Quebec Longitudinal Study of Child Development (Canada). Children were individually assessed for cognitive skills and teachers rated their classroom attention skills at 65 months. Outcome measures include health behaviors, psychosocial, and academic outcomes at 122 months. Multiple regression analyses were used. Results . Receptive vocabulary in kindergarten exclusively predicted fourth-grade dietary habits. Unstandardized coefficients predicted decreases in sweet snack intake (β = −.009, 95% confidence interval [CI] = −.011 to −.006) and dairy product intake (β = .009, 95% CI = .005 to .013). Conversely, higher kindergarten math skills predicted increases in activities requiring physical effort (β = .030, 95% CI = .011 to .056). Although vocabulary and attention skills were found important, kindergarten math skills were stronger and more consistent predictors of later academic outcomes. Conclusions . From a population-health perspective, the skills children bring to the kindergarten classroom might reduce a host of lifestyle risks from childhood through adulthood. Early promotion of such skills also offers possibilities for ultimately reducing later disparities in health and education.